Edukasi Pemanfaatan Bawang Putih Dalam Menurunkan Tekanan Darah pada Menopause di PMB Soraya Palembang - Devina Anggrainy Dencik (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Hypertension is a degenerative disease that appears in old age, it is also called the silent killer because it causes serious illnesses. The risk of hypertension increases in postmenopausal women due to a decrease in the hormone estrogen. One non-pharmacological effort to lower blood pressure is consuming garlic. The substances allicin and hydrogen sulfide in garlic work to enlarge blood vessels and make them less stiff so that blood flow becomes smooth and lowers blood pressure. The aim of the activity is to increase menopausal women's knowledge about the benefits of garlic in lowering blood pressure. Extension method with Question and Answer Lectures and Educational Videos. There were 18 counseling participants. The results of the activity showed an increase in participants' knowledge as measured by pre- and post-extension questionnaires. The average knowledge score at the pretest was 57.2 and the average knowledge score at the posttest was 72.2. It is hoped that menopausal women who experience hypertension can use garlic to lower blood pressure according to the recommended dose.